Extracts of renealmia alpinia (rottb.) MAAS protect against lethality and systemic hemorrhage induced by bothrops asper venom: Insights from a model with extract administration before venom injection (2023)
Renealmia alpinia (Rottb.) MAAS, obtained by micropropagation (in vitro) and wild forms have previously been shown to inhibit some toxic activities of Bothrops asper snake venom if preincubated before injection.